Identification of mutation in the RET gene in a patient with medullary thyroid cancer - Hà, Nguyễn Hải; Yến, Trần Thị Hải; Nhung, Vũ Phương; Thương, Ma Thị Huyền; Tôn, Nguyễn Đăng; Hải, Nông Văn (Vietnam Journal of Biotechnology, 2016)
Medullary thyroid carcinoma (MTC) is a type of tumors drived from thyroid parafollicular cells (C-cells), comprises 5–10% of all thyroid malignancies. About 25% of MTC cases occur as an autosomal dominant heredited disorder which is mostly caused by activating mutations of RET pro-oncogen and they occur as components of the multiple endocrine neoplasia type 2 syndromes (MEN 2A and 2B) or familial MTC. The guidelines for genetic testing in MTC of the European Thyroid Association recommend that exons 5, 8, 10, 11, 13, 14, 15 and 16 should always be screened starting in patients. This study aims to identify the genetic causes of a male patient diagnosed with MEN2 and pheochromocytoma. Genomic DNA was extracted from peripheral blood of patient. Eight recommened exons (5, 8, 10, 11, 13, 14, 15 and 16) of the RET gene were amplified by PCR and sequenced by Sanger method on the ABI 3500 genetic annalyzer. The results showed a heterozygous C to T transition at nucleotide 2753 in exon 16 of the RET gene. The c.2753 C>T transition resulted in a missense mutation of methionine to threonine (p.M918T) in the RET protein. This mutation was located in the intracellular tyrosine kinase domain of protein and has been reported in 95% of MEN2B cases, therefore, it would be the causative mutant of our patient. Our patient harboring a pM918T germline mutation and there is a 50% probability that he will pass this mutation to a child. Thus, his six-year-old boy with normal health status was advised to have the genetic test for this mutation. The results showed that he had not inherited the mutation c.2753T> C from his father